Connecting Medical Personnel to Dentists via Teledentistry in a Children's Hospital System: A Pilot Study - Hammersmith, Kimberly J.; Thiel, Macaire C.; Messina, Matthew J.; Casamassimo, Paul S.; Townsend, Janice A. (Frontiers in Oral Health, 2021)
Investigators evaluated feasibility, acceptability, and sustainability of a teledentistry pilot program within a children's hospital network between March, 2018, and April, 2019. The program connected dentists to medical personnel and patients being treated in urgent care clinics, a primary care clinic, and a freestanding emergency department via synchronous video consultation. Three separate but parallel questionnaires evaluated caregiver, medical personnel, and dentist perspectives on the experience. Utilization of teledentistry was very low (2%, 14/826 opportunities), but attitudes regarding this service were largely positive among all groups involved and across all survey domains. Uptake of new technology has barriers but teledentistry may be an acceptable service, especially in the case of dental trauma.